Thoracic faun tail associated with spinal dysraphism. - Jagadishkumar, K.; Harshini, K.G.; Manjunath, V.G.; Pratham, Mehta (European Journal of Pediatric Dermatology, 2025)
Spinal dysraphism is a congenital condition involving spine, spinal cord, or nerve roots. Spinal dysraphism may be associated with cutaneous markers in more than half of cases, which include lipoma, dermal sinus, hypertrichosis, dimple, hyperpigmentation and capillary haemangioma. Faun tail is a well-defined area of congenital hypertrichosis, typically triangular or cicumscribed situated over the lumbosacral region. Faun tail itself is rare; its location at thoracic level is even rarer. Here with we are reporting 14 months old baby with 2 cutaneous markers, Faun tail at thoracic region along with sacral dimple associated butterfly vertebrae and diastematomyelia of T5-T6.